The Unequal Impact of the COVID Pandemic: Theory and Evidence on Health and Economic Outcomes for Different Income Groups - Cécile Aubert; Hai-Anh Dang; Manh-Hung Nguyen (Institute of Labor Economics (IZA), 2022)
This paper studies how wealth and health inequalities have interacted with the Covid-19 epidemic in a way that has reinforced inequalities in income, savings, epidemic risk and even individual preventive behaviors. We present in more detail two papers and their theoretical and empirical results. Recovery and contamination rates are functions of an individual's health status and capacity to access quality healthcare. Poorer individuals, who face budget constraints, have a higher risk of loosing their income because of contamination. Data on six countries confirm a disproportionate impact of the epidemic on the poorest 60% of the population.
Keywords: D0; H0; I1; I3; O1; 330; behavior changes; healthcare; income quintiles; poverty; COVID-19